The Effect of Tax Planning Strategies and Compliance with Digital Tax Regulations on Effective Tax Burden and Financial Performance of Start-ups in Jakarta - Judijanto, Loso; Nurhayadi, Willy; Kristanto, Eri; Barus, Irwan Irawadi; Munzir, Munzir (Westscience Press, 2025)
This study investigates the impact of tax planning strategies and compliance with digital tax regulations on the effective tax burden and financial performance of start-ups in Jakarta. Using a quantitative approach, data were collected from 130 start-up respondents through a structured questionnaire with a Likert scale ranging from 1 to 5. Data analysis was conducted using Structural Equation Modeling–Partial Least Squares (SEM-PLS 3). The results show that tax planning strategies significantly reduce the effective tax burden and positively influence financial performance. Compliance with digital tax regulations also reduces the effective tax burden and enhances financial performance, highlighting the importance of aligning with Indonesia’s digitalized tax system. Furthermore, the effective tax burden was found to have a significant negative effect on financial performance and mediates the relationships between tax planning, compliance, and financial performance. These findings suggest that start-ups can achieve fiscal efficiency and strengthen their competitiveness by integrating proactive tax planning with digital tax compliance.